Sytuacja prawna pracownika powracającego do pracy po wykorzystaniu urlopów związanych z rodzicielstwem - uwagi de lege ferenda - Czerniak-Swędzioł, Justyna (Studia z Zakresu Prawa Pracy i Polityki Społecznej (Online), 2017)
Labour law provisions meet the expectations of employees who are also parents and enable them to connect a professional work with parental responsibilities. There is always a guarantee of employment granted by employer to the employee after returning from parental leave and that is because of an articles 183² and 1864 of the Polish Labour Code which protect these employees. The protection is also granted to the employee who is entitled to a parental leave but he or she decides to lower his or her workload what is considered as alternative form of parental leave. If employee returns to work for his or her employment in a previously given post, equivalent post or other in accordance with his or her qualifications it should not adversely affect his or her financial situation. These labour law provision guarantees a salary which he or she would receive if he or she would not use a parental leave. These provisions do not forbidan employer to provide notice of changing termination or defi nitive termination, but as long as there is a possibility of mandate other work to the returning employee, definitive termination is not justified. The subject of analysis are valid labour law provisions in order to verify if assumption of the legislator about stabilization of employment for employees who are also parents returning to work after parental leave is fully implemented in practice. In conclusion, in relation with expanding the range of application article 186 (8) § 2 of the Polish Labour Code by jurisprudence, the position of an employee returning to work aft er using parental leave has been weakened.